IDENTIFICATION OF THREATENED AND ENDEMIC ANGELICA GLAUCA: INSIGHT FROM DNA BARCODING AND PHYLOGENETIC ANALYSIS - Sajjad; Khushi Muhammad; Mohammad Islam; Hamid Ali; Shakila Umer; Ayesha Azeem; Shafee ur Rehman; Irfan Ullah (Journal of Animal and Plant Sciences, 2026)
Angelica glauca Edgew is a perennial non-vascular herb belonging to the family Apiaceae, having a high medicinal and economic value. However, A. glauca faces threats from climate change, habitat loss, and overharvesting, which reduce its natural populations. To address these issues, the DNA barcoding technique was employed as a taxonomic tool to confirm the accurate identification and support the conservation of this species. 2% CTAB was used to extract total genomic DNA, andDNA barcode markers such as (ITS2, matK, rbcL, and rpoB) were amplified and sequenced. Nucleotide sequence analysis of Angelica species revealed that the conserved, parsimony-informative, and singleton sites vary from primer to primer. The highest number of variable sites was recorded at 192 in the matK marker, followed by 170 in the rpoB marker. A phylogenetic tree was generated through the neighbour-joining method. It showed that A. glauca, based on the ITS2 sequence (LC860493), was closely clustered with A. archangelica-MT735413.1, based on matK (LC860494), with A. archangelica-GQ248079.1 based on rbcL (LC860492), with A. archangelica-GQ248549.1, and based on rpoB (LC593680) with A. megaphylla-NC057128.1, with bootstrap support of 63, 70, 100, and 43, respectively. The present study concluded that A. glauca is closely related to A. archangelica within the genus Angelica, and the markers used in this study are recommended for improved identification and conservation of other threatened or endangered plant species.
Keywords: Angelica glauca; Endemic; Threatened; Himalayan; DNA barcoding; and Phylogeny.